A Structured Ultramicroporous Metal‐Organic Framework for Carbon Dioxide Capture†. Issue 7 (13th February 2023) - Wang, Shao‐Min; Liu, Hao‐Ran; Ni, Shuang; Yang, Qing‐Yuan
Comprehensive Summary: Carbon dioxide (CO2 ) capture is one of the most important aspects of reducing global warming. In terms of CO2 capture, metal‐organic frameworks (MOFs) have several advantages. However, it isn't easy to shape MOFs while maintaining their performance. Herein, we describe the development of a pellet‐shaped ultramicroporous MOF, Ni(3‐ain) 2 (3‐ain = 3‐aminoinoisonicotinic acid), that is capable of selectively adsorbing CO2 . Polyvinyl butyral (PVB) is used as a binder during the production of Ni(3‐ain) 2 MOF pellets. The adequately shaped material can maintain its crystallinity and exhibit a high CO2 adsorption capacity (3.73 mmol·g –1 ) at ambient conditions, which is significantly greater than those obtained for N2 (0.63 mmol·g –1 ) and CO (0.90 mmol·g –1 ). Consequently, this material displays high IAST selectivities for CO2 /N2 (26.3, 15/85, V / V ) and CO2 /CO (19.2, 1/99, V / V ). According to the theoretical calculations, Ni(3‐ain) 2 preferentially adsorbs CO2 molecules over N2 molecules and CO molecules. The results of experiments on dynamic breakthrough have demonstrated that Ni(3‐ain) 2 pellets are capable of effectively separating CO2 /N2 or CO2 /CO mixtures under conditions of dynamic flow. Furthermore, the structured MOF materials can be synthesized in one step at kilogram scale. This work provides an avenue for the shaping of MOFs for potential industrial applications in the future. Abstract :